Sensitivity of some palm cultivars Phoenix dactylifera for the infection of scale insect Parlatoria blanchardi (Targ.) On the palm with an eval-uation of the efficiency of the seven-point Ladybird Coccinella sep-tempunctata L. in Al Muthanna Governorate - Al Hamadani, Alaa Hussein Abed (Journal of Kerbala for Agricultural Sciences, 2018)
The search carried out in 2017 , a field stud was conducted in the region of ​​Al-Suhour / Al-Rumaitha district / Muthanna province to calculate the sensitivity of some palm varieties to the infection of the scale insect Parlatoria Blanchardi , and laboratory study to evaluate the efficiency of the seven-point coccinella septempunctata against the different roles of the insect , The results of the field study to palm cultivars studied of ten palm cultivars which as follows (Shweithi, Prem, Gozzy, Shukar, Omrani, Maktoom, Khadraoui, Balga, Derri and Zahdi) showed that the two varieties Shweithi and Prem were more sensitive to infection to insect . It has reached the final rate of insects per 1 cm2/ Cousins and for the three months 22.62 and 17.92 for the two varieties above, respectively. While the derri and zahdi were less susceptible to insect infection. It has reached the final rate for the three months was 4.75 and 3.75 insect .1 cm-2 Cousins respectively. The results of the statistical analysis showed significant differences in the susceptibility of these varieties to infection of the insect, this indicates that there is a dietary preference for the insect among these varieties. The results of the laboratory study showed that the different larvae ages of the seven-point C. septempunctata had fed on all the roles of the white scale insect P. blanchardi and that the total number of eggs, nymphs and insect adults was 1049.7, 349.3 and 109 respectively. The fourth-year larvae of the Ladybird were more efficient than other ages , The results also indicated that Ladybird adults were fed to all insect roles and the average number of eggs, nymphs and predatory adults reached 541, 291.7 and 131, respectively. The results showed that larvae and Ladybird adults were highly efficient in reducing the numerical density for all The insect roles, and its Predatory efficiency on insect eggs and nymphs were more than adults.